2001
DOI: 10.1128/aac.45.9.2635-2637.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antifungal Activities of the New Triazole UR-9825 against Clinically Important Filamentous Fungi

Abstract: We used a modified reference microdilution method (the M-38P method) to evaluate the in vitro activities of the new triazole UR-9825 in comparison with those of amphotericin B against 77 strains of opportunistic filamentous fungi. UR-9825 was clearly more active than amphotericin B against all fungi except Fusarium solani and Scytalidium spp. Notably, UR-9825 had low MICs for Aspergillus fumigatus and Paecilomyces lilacinus (MICs at which 90% of isolates are inhibited, 0.125 g/ml for both species).The incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
18
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 16 publications
4
18
0
2
Order By: Relevance
“…For P. lilacinus only the novel azole derivatives, and especially RVZ, were active. These results generally confirmed our earlier studies (1,3) and those of other authors (7).…”
supporting
confidence: 83%
“…For P. lilacinus only the novel azole derivatives, and especially RVZ, were active. These results generally confirmed our earlier studies (1,3) and those of other authors (7).…”
supporting
confidence: 83%
“…The antifungal activity of AMB obtained here agrees with those found by other investigators (4,11,13). In a previous study we reported AMB MICs similar to those obtained here (MIC 90 , 9.23 g/ml at 72 h of incubation), even though the results were generated by the macrodilution method.…”
Section: Discussionsupporting
confidence: 83%
“…The new triazole albaconazole (ABC) showed good in vitro activity against this fungus in a recent study which tested 30 strains (5). This drug has also shown good in vitro activity against dermatophytes, Aspergillus, Paecilomyces, and Candida species, among others (4,8,19). The concentrations of this drug achieved in plasma of mice are very low, and its half-life is short; however, its pharmacokinetics and bioavailability are excellent in rabbits (1).…”
mentioning
confidence: 99%